2014
DOI: 10.1517/14656566.2014.955469
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine in the treatment of opioid addiction: opportunities, challenges and strategies

Abstract: Buprenorphine can align addiction treatment with treatments for other chronic medical illnesses. However, preventing diversion will require graduate and continuing medical education and integrated care models for delivery of buprenorphine to those in need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 77 publications
0
23
0
1
Order By: Relevance
“…[8][9][10] The only other national survey of physicians providing buprenorphine maintenance treatment 13 found that physicians with waivers whose names were found on a public locator list and those whose names were not reported financial concerns (59.3% and 71.8%, respectively), more often than they reported diversion concerns (18.7% and 26.3% respectively). Our findings show the opposite trend: more physicians, regardless of prescribing status, were concerned about diversion than finances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] The only other national survey of physicians providing buprenorphine maintenance treatment 13 found that physicians with waivers whose names were found on a public locator list and those whose names were not reported financial concerns (59.3% and 71.8%, respectively), more often than they reported diversion concerns (18.7% and 26.3% respectively). Our findings show the opposite trend: more physicians, regardless of prescribing status, were concerned about diversion than finances.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A few studies, limited to 1 or only a few states, have looked at the barriers physicians face providing buprenorphine maintenance treatment, but none has examined nationally the differences between physician groups who are and are not actively using their waivers or accepting new patients. [7][8][9][10] This study's purpose was to understand the barriers physicians with waivers face in providing buprenorphine maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As is true with most pharmacotherapies for substance use disorders, one’s view of the effectiveness of buprenorphine depends on the question, “Compared to what?” There is no question that office-based buprenorphine treatment has been a significant advance in broadening the availability of an effective treatment for opioid dependence and has saved countless lives (912). Numerous reviews and meta-analyses underscore the strong effectiveness of buprenorphine in enhancing treatment retention and reducing illicit opioid use with respect to placebo or no treatment (13, 14).…”
Section: Overview Of the Four Trials Showing No Benefit Of Adding Coumentioning
confidence: 99%
“…Numerous reviews and meta-analyses underscore the strong effectiveness of buprenorphine in enhancing treatment retention and reducing illicit opioid use with respect to placebo or no treatment (13, 14). Buprenorphine’s important benefits also include reduced risk of HIV, sexually transmitted diseases, medical costs, and mortality (9). …”
Section: Overview Of the Four Trials Showing No Benefit Of Adding Coumentioning
confidence: 99%
“…Importantly, between 2006 and 2010 (the time period during which our sample was recruited), only 8% of SUD treatment programs offered medication-assisted treatment (SAMHSA, 2011). Emerging evidence regarding the efficacy and safety of the partial agonist buprenorphine/naloxone (Gray, 2007; Li et al, 2014; Mattick et al, 2014) and intramuscular extended release formulation of the antagonist naltrexone (Gastfriend, 2011), may shift clinical perspectives, leading to greater likelihood of referral for SUD medication. For example, among SUD treatment seekers in 2012, 28% of primary heroin and 18% of primary non-heroin opioid patients reported engagement with medication-assisted treatment (SAMHSA, 2014).…”
Section: Discussionmentioning
confidence: 99%